CORPORATE SOCIAL RESPONSIBILITY PADA INDUSTRI PERBANKAN SYARIAH DI INDONESIA - Ahmad Rizal Solihudin (Optimum: Jurnal Ekonomi dan Pembangunan, 2017)
The paradigm of sustainability development developed by Bank Indonesia is in line with the principles used in corporate social responsibility (CSR). This study aims to map and analyze performance of CSR in Islamic banking industry in Indonesia. The methods of data collection using observation in annual reports with content analysis techniques. To analyze relationship between variables, in this study used data analysis tool with multiple linear regression analysis. The examine result proves that level of profitability of sharia banks significantly affect performance of CSR activities. While the size of the company and corporate governance proxied by the existence of independent commissioners did not give a significant effect on performance of Islamic banking CSR in Indonesia